Analyzing the shear strength of Kaolin clay stabilized with polypropylene columns - Hoque, Md. Ikramul; Muzamir, Hasan; Muhammad Syamsul Imran, Zaini; Almuaythir, Sultan (Springer Nature, 2026)
Soft soil presents significant challenges for infrastructure development because of its high compressibility, low bearing capacity, and lateral deformation. Granular column techniques can reduce settlement in soft and weak soil by speeding up the dissipation of excess pore water pressure and enhancing bearing capacity. Furthermore, by stopping the lateral deformation of the clay particle, the use of reinforcing columns can greatly increase the shear strength of soft soil. The primary goal of this study is to find out how polypropylene columns can improve the soft reconstituted kaolin clay’s compressibility and shear strength. A number of factors, including the area replacement ratio, height penetration ratio, and volume replacement ratio, were analysed in order to look at the strength characteristics. This examination encompassed both single and grouped polypropylene columns. The reinforced kaolin samples were assessed using the Unconfined Compression Test. Based on the UCT results, it was observed that the undrained shear strength generally improved as the height penetrating ratio increased, however, once it reached 100% height penetrating ratio, it began to decrease. The undrained shear strength increment was also influenced by the polypropylene area replacement ratio. The shear strength of the soil sample did not change despite its high area replacement ratio. As the soil sample’s circumference was smaller than required, the column’s shearing strength needed to be increased. The ratio increased as the strength increased in the absence of restricting pressure. However, as the remaining width of the soil sample became insufficient to support the columns, excessive area replacement reduced the shear strength of the sample reinforced by group columns. In general, it can be concluded that the installation of polypropylene columns has the potential to improve the shear strength and compressibility characteristics of soft clay.